IMPLEMENTATION OF THE PRACTICUM METHODS WITH GUIDED-DISCOVERY MODEL TOTHE STUDENT SKILL OF SCIENCE PROCESS - Hayati, Dwi Puji; Bintari, Siti Harnina; Sukaesih, Sri (FMIPA UNNES, 2019)
Biology learning in SMA N 2 Batang still emphasized cognitive ability, has not yet oriented on the development of student skill of science process. The purpose of this research is to analyze theimplementation of practicum methods with guided-discovery model on students skill of science process. This research is Pre-Experimental with Pre-Test and Post Test Group Design. The sample was determined by purposive sampling, X MIPA 1 and X MIPA 2 as experiment class-1 and -2. The results obtained from the test and non-test. The result of skill of science process test was analyzed by N-gain. The average of N-gain test result from the experimental class is 11,4% in high category, 64,3% in medium category, and 24,3% in low category. Analysis of post-test result and student observation result in good category. The success of this method implementation in MIPA 1 is 95,15% and MIPA 2 is 88,9% with very high category. Students and teachers respond well to the implementation of practicum method with guided-discovery model. The conclusion of this research is the implementation of practicum method with guided-discovery model of environmental change material can develop student skill of science process in observing, classifyng, predicting, measuring, concluding, and communicating aspects.